Bilateral apex pubis distance：a novel index for follicular development and egg laying status in domestic hens (Gallus gallus domesticus). Issue 2 (3rd March 2020) - Yang, L.; Mo, C.; Adetula, A. A.; Elokil, A. A.; Akbar Bhuiyan, A.; Huang, T.; Li, S.
ABSTRACT: 1. Measures of the bilateral apex pubis (BAP) in White Leghorn (WLH) hens aged from 16 to 64 weeks (from the time ovaries were completely undeveloped to senility) were ranked into various groups so the relationship between external traits (BAP distance, comb length, comb height, wattle length, wattle height, body weight) and internal traits (largest ovarian follicle diameter (LFD) and oviduct weight and length) could be determined. 2. Using correlation and regression analysis with data from 16 weeks of age to the onset of lay, measurements of the apex pubis showed a strong correlation with LFD (r = 0.80, P < 0.01) and oviduct weight (r = 0.80, P < 0.01). 3. Multiple comparisons among WLH hens from 16 to 43 weeks of age showed that the BAP distance increased in all groups ranked by LFD or by laying period. 4. In the late laying period (>60 weeks of age), BAP distance showed a significant decrease (P < 0.01) in long-term non-laying hens compared to laying hens. 5. These findings suggest BAP distance can serve as an index for evaluating the onset and probable stages of follicular development during sexual maturation and/or aid in the identification and selection of non-laying hens during reproduction.